Assessment of Knowledge Regarding Safety Profile, Use, and Boxed Warnings of Fluoroquinolones Among Healthcare Professionals in Saudi Arabia: A Potential Implication for Drug Regulatory Authorities - Mallhi, Tauqeer Hussain; Alanazi, Abdullah Salah; Khan, Yusra Habib; Alotaibi, Nasser Hadal; Salman, Muhammad; Alzarea, Abdulaziz Ibrahim; Khan, Salah-Ud-Din; Alruwaili, Nabil K.; Alenazi, Alaa Salah; Alatawi, Ahmed D.; Iqbal, Zafar; Butt, Muhammad Hammad; et al. (Frontiers in Medicine, 2022)
Background Despite a series of “boxed warnings” (BWs) issued by the US Food and Drug Administration (FDA), fluoroquinolones (FQs) are among the most prescribed antibiotics across the world. Moreover, few studies demonstrated that BW of FQs had less or no impact on prescribing patterns among healthcare professionals (HCPs), which might be attributed to the lack of knowledge toward such warnings. Since FQs contribute to a major proportion of antimicrobial prescriptions in the Kingdom of Saudi Arabia (KSA), this study aimed to ascertain the extent of knowledge toward safety profile, use, and BW of FQs among HCPs working in the KSA. Methods This cross-sectional study (May–August 2021) was conducted among HCPs working in KSA through a validated questionnaire. The HCPs were requested to identify the indications, adverse effects (AEs), and BW of FQs. The knowledge score (out of 40) was estimated among participants, and its association with demographics was ascertained through the chi-square test, Student's t-test, or Mann-Whitney U-test and one-way ANOVA, or Kruskal-Wallis test, where appropriate. Results Of the 573 participants (age: 36.1 ± 10.6 years, men: 59.7%), 262 (45.8%) were prescribers reporting frequent use of ciprofloxacin, levofloxacin, and ofloxacin. One-fourth (25.6%) of the prescribers did not recognize nalidixic acid as an agent from FQs class. About 60% of participants correctly identified the mechanism of action of FQs. The average knowledge score was 14.8 ± 6.4, where only 21.5% of respondents scored ≥50%. The average knowledge score for indications, AEs, and BW domains was 5.29 ± 3.05, 6.17 ± 4.05, and 2.3 ± 1.5, respectively. Only 75 (13.1%) participants recognized half of the BW, and 38.6% of participants identified at least one warning. The HCPs aged >40 years (p = 0.043), having non-Saudi's nationality (p < 0.001), working in Riyadh and Eastern regions (p < 0.001), having pharmacy and medicine disciplines (p < 0.001), practicing in public sectors (p = 0.004), and having more than 10 years of experience (p < 0.001) were significantly associated with high knowledge score. Conclusion This study demonstrates the unsatisfactory knowledge toward safety profile, use, and BW of FQs among HCPs which may put patients at increased risks of AEs. The knowledge score differed among various socio-demographic groups. There is a dire need to initiate the antimicrobial-focused educational campaigns among HCPs regardless of their specialties and methods to improve education and disseminate FDA warnings in practice.